The Use and Value of Urban Geology in Canada: A Case Study in the National Capital Region - Bélanger, J. Robert; Moore, Charles W. (Geoscience Canada, 1999)
In response to a request to increase its activities in environmental geology and to collaborate with the provinces, the Geological Survey of Canada (GSC) initiated a project in 1993 to provide geoscience information for urban and regional planning and development in eastern Ontario and western Quebec. Prior to the launch of the project, representatives from various levels of government, private consultants, environmentalists, universities and the general public were invited to a forum to discuss the need for and usefulness of urban geological information. The participants confirmed the importance of urban geological information and supported a co-ordinating role for the GSC. Following this forum Natural Resources Canada’s Audit and Evaluation Branch undertook an impact study that examined the usefulness and value of benefits of basic types of geoscience information in urban and regional planning and development. The evaluation study of the National Capital Region Project determined that geoscience documents are used extensively and provide an authoritative standard for work. They are particularly useful in preliminary project planning, geotechnical engineering for major facilities, environmental impact assessments, public safety planning, and as a multi-disciplinary research tool and field guide. The estimated value of benefits includes a 5%-20% reduction in the cost of civil/environmental engineering design and planning study work, and considerable monetary savings in derived or indirect benefits, amounting to annual savings of several million dollars. Recent technological advances increase the possible range of applications, especially for those who have traditionally been users of geological maps. Résumé Suite à une requête adressée à la Commission géologique du Canada pour qu’elle augmente ses activités en géologie de l’environnement et qu’elle collabore plus étroitement avec les provinces, celle-ci a lancé, en 1993, un projet visant à fournir de l’information géoscientifique pour l’aménagement urbain et régional dans l’Est ontarien et l’Ouest québécois. Lors du lancement du projet, on a invité des représentants des différents paliers de gouvernements, des experts-conseils, des environnemental istes, des universitaires et des gens du publique en général, pour discuter de la pertinence du projet de géologie urbaine. Les participants ont souligné de façon unanime l’importance des données géologiques en aménagement du territoire et ont appuyé le rôle de coordonnâtes de la Commission géologique en ce domaine. Dans un deuxième temps, la Direction de la vérification et de l’évaluation du Ministère des Ressources naturelles Canada a entrepris une étude d’impact pour déterminer l’utilité et la valeur des données géoscientifiques fondamentales dans l’aménagement régional. L’étude du cas de la Capitale nationale a démontré que les documents géoscientifiques sont utilisés de façon extensive et fournissent des normes officielles acceptées. Les données sont particulièrement utiles pour la planification des projets, les travaux d’ingénierie pour les installations publiques, pour les études d’impact sur l’environnement, pour la sécurité publique et enfin servent d’outil de recherche multidisciplinaire et de guide sur le terrain. La valeur estimée des bénéfices inclut une réduction de 5%-20% des coûts dans la planification des études de génie civil et environnemental, ainsi que des économies indirectes pouvant atteindre plusieurs millions de dollars annuellement. Les développements récents en informatique permettent d’étendre l’utilisation des données géoscientifiques à de nouveaux domaines, bénéficiant principalement, aux utilisateurs traditionnels des cartes géologiques.